THE INFLUENCE OF THE DISTILLATION PROCESS ON THE CONTENT OF METALS IN HOME- AND INDUSTRIALLY-BREWED ALCOHOLIC BEVERAGES – RISK ASSESSMENT TO HUMAN HEALTH - MUNTEAN, Norbert; FRENȚIU, Tiberiu; RÁKOS, Gábor; COVACI, Enikő (Studia Universitatis Babeș-Bolyai Chemia, 2022)
The aim of this study was to assess the influence of the distillation processes on the content of Al, Ca, Cd, Co, Cr, Cu, Fe, Mg, Mn, Ni, Pb and Zn in 18 home-brewed fruit spirits, originating from different locations of Romania, and 3 industrially-brewed spirits and 19 cognacs. Metals quantification was achieved by inductively coupled plasma optical emission spectrometry (ICP-OES) after sample digestion. The study revealed higher metals concentration in the home-brewed spirits, compared to the industrially-brewed ones, with concentrations of Cu, Fe, Al and Zn in most of the samples above the Alcohol Measures for Public Health Research Alliance (AMPHORA) project set threshold in recorded alcoholic beverages. However, no risk to human health was found by a moderate consumption of the analyzed alcoholic beverages (100 mL/day) as respects to long-term non-carcinogenic health risk. The Principal Components Analysis (PCA) indicated a wide dispersion of the analyzed alcoholic beverages according to their elemental composition. The two-dimensional PCA representation after Varimax rotation indicated a group of elements of natural origin (Ca, Mg, Al, Cd, Mn, Pb), and another of trace elements (Co, Cr, Ni, Zn, Fe) originating from the distillation equipment. Copper however, was associated both with the raw material and the distillation equipment.